Pengaruh Massa Dan Waktu Kontak Adsorben Dari Tanah Gambut Dalam Penyisihan Logam Besi (Fe) , Logam Mangan (Mn) Dan Warna Pada Air Gambut - Mila Safitri; Edward HS; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Peat soil as an adsorbent in peat water treatment is located in Sabak Permai Village, Sabak Auh District, Siak Regency. This study aims to study the effect of mass variation and contact time of peat soil adsorbent on the efficiency of Fe, Mn and color removal in peat water. The experiment was carried out by adsorption at a speed of 125 rpm by varying the mass (5, 10, 15, 20 g/L) and contact time (120, 150, 180, 210 minutes). While the fixed variables are 10% Phosphoric Acid Activator, 3000C Heating and 80 mesh particle size. The concentration of iron metal removal (Fe) was 0.449 mg/L with a percentage of 88.66%, Manganese (Mn) was 0.081 mg/L with a percentage of 90.75% and color removal in peat water was 380.5 PtCo. with a percentage of 71.5%. The adsorption capacity of peat water on Fe metal is 3.618 mg/gr, Manganese Mn is 0.796 mg/gr and color 1.259 mg/g organic matter is 294.2 mg/gr and iron (Fe) is 3.91 mg/gr at a mass of 20 grams and a time of 210 minutes. Keywords: Peat Soil, Peat Water, Adsorption, Removal Efficiency, Adsorption Capacity